Pelaksanaan Eksekusi Barang Jaminan Pada PT. Nusa Surya Ciptadana Cabang Soe Dalam Perspektif Undang-Undang Nomor 42 Tahun 1999 Tentang Jaminan Fidusia - Selan, Dicky Kolodikson; Hedewata, Agustinus; Dinata, Husni Kusuma (Artemis Law Journal, 2024)
Consumer financing is an agreement between a finance company and a consumer. The existence of financing institutions in legislation number 42 of 1999 in relation to the provision of guarantees if consumers or debtors neglect obligations or default creditors can carry out execution of fiduciary collateral objects. However, in practice, in making withdrawals and sales, there is still often legal uncertainty and balance between the debtor's rights and creditors' benefits from the results of the execution of fiduciary guarantees. The benefit of the research is as a reference for writers and information for the public regarding the process of executing collateral, especially fiduciary guarantees. The results of this study show that the legal consequences that arise are that debtors who default due to creditor agreements have the right to take collateral and sell under the hands without the debtor's knowledge and are not notified of the proceeds of the sale of collateral resulting in legal uncertainty and imbalance between the debtor's rights and the benefits obtained by creditors.